Effect of pre and post-slaughter processes on meat characteristics of Santa Ines ewes discarded due to age - Santos,Luiz Eduardo dos (2012)
The effects of body condition recovery (BC), carcass electrical stimulation (ES), aging time (AT 7 - 14 days), and calcium chloride injection on the meat characteristics of Santa Inês ewes (±5 years old) slaughtered immediately after weaning or after the body condition recovery period were studied. The carcass temperature, pH, shear force (SF), cooking loss (CL), meat color (L*, a*, b*), and meat tenderness were evaluated. A completely randomized design in a 2 × 2 × 2 × 3 (BC × ES × CaCl2 × AT) factorial arrangement was used, and the sensory tenderness data were analyzed using the table of Minimum Number of Correct Answers for the Duo-Trio test. The body condition recovery reduces the shear force in 8%, increasing their tenderness. Electrical stimulation reduced the shear force (24%) and did not change the other parameters. The aging time (7 or 14 days) decreased the shear force (18-26%), effect that was enhanced by electrical stimulation, and it darkened the meat reducing lightness (L*) and increasing yellowness (b*). The treatment with CaCl2 was the most effective in tenderizing meat by reducing the shear force ( 35%); increasing the cooking loss (4.5%); and increasing L* and b* lightening the meat. The sensory evaluation of tenderness corroborates the findings of the experimental evaluation regarding the effect of the treatment with CaCl2 on the meat quality improvement. It was concluded that the treatments improve meat characteristics achieving better results when applied together.